Investigação de propriedades relacionais e funcionais de estímulos a partir da relational frame theory - Margarete Schmidt (2021)
This thesis presents four experimental studies assessing functional and relational properties of coordinating stimuli through the Implicit Relational Assessment Procedure (IRAP). Each experiment has a delimited specific purpose but the general one for them is to investigate the functional and relational properties of the stimuli involved. The initial part of the thesis provides a brief introduction in Relational Frame Theory. For Experiment 1, there is an investigation about the dynamic of Arbitrarily Applicable Relational Responding (AARR) involving emojis and pseudowords. This experiment used the matching-to-sample procedure as well as the IRAP. The result of the analysis was that the happy emoji has a major force of orientation than that of the angry emoji, which shows that the happy stimulus has more power of orientation, evocation and motivation than the angry one. The Experiment 2 was developed to investigate the influence of Relating, Orienting, Evoking and Motivating (ROE-M) in an IRAP experiment, contrasting stimuli pairs with opposite behavioral functions. Tattooed soccer fans from two historical rival teams were to provide true/false answers in an IRAP for the name of the team (label) and the team symbol (target). The result was that the behavioral functions of the stimuli were more effective in producing the IRAP effect than the relational ones, showing that the power of orientation, evocation and motivation of certain stimuli can surpass the relational force between them. The purpose of the Experiment 3 is to assess the Arbitrarily Applicable Relational Responding (AARR) involving the forename and pairs of opposing adjectives written in two different languages to identify whether there is or not a major functional and relational bias when stimuli in a native or foreign language are coordinated, based on the native language of the participant of the experiment. Starting with an analysis interpreted through the DAARRE model, it was possible to notice the single-trial-type-dominance-effect (STTDE) highlighting a pro-native language attitude. Making use of the DAARRE model and the HDML structure, the Experiment 4 presents a study analyzing how the nature and position of stimuli in an IRAP influence the IRAP effect differently. This study used “happy face” and “angry face” pre-experimental stimuli, the words “joy” and “anger” and the “true/false” answers in two different IRAP programs. They have only to invert the position of the label and target in coordinated stimuli. The eye tracking evaluation was undertaken with the RealEye online tool. The results pointed out that the position of the stimuli in an IRAP does not impact the IRAP effect and that the pre-experimental stimuli has a great relational force that stops the Dissonant Target Trial Type Effect (DTTTE) from arising, as observed in previous studies.